NMR hyperpolarization techniques of gases - Barskiy, Danila A.; Coffey, Aaron M.; Nikolaou, Panayiotis; Mikhaylov, Dmitry M.; Goodson, Boyd M.; Branca, Rosa T.; Lu, George J.; Shapiro, Mikhail G.; Telkki, Ville-Veikko; Zhivonitko, Vladimir V.; Koptyug, Igor V.; Salnikov, Oleg G.; et al. (Wiley-VCH Verlag, 2017)
Nuclear spin polarization can be significantly increased through the process of hyperpolarization, leading to an increase in the sensitivity of nuclear magnetic resonance (NMR) experiments by 4–8 orders of magnitude. Hyperpolarized gases, unlike liquids and solids, can often be readily separated and purified from the compounds used to mediate the hyperpolarization processes. These pure hyperpolarized gases enabled many novel MRI applications including the visualization of void spaces, imaging of lung function, and remote detection. Additionally, hyperpolarized gases can be dissolved in liquids and can be used as sensitive molecular probes and reporters. This Minireview covers the fundamentals of the preparation of hyperpolarized gases and focuses on selected applications of interest to biomedicine and materials science.